Binary opposites – can South African journalists be both watchdogs and developmental journalists?. (1st March 2016) - De Beer, Arnold S.; Malila, Vanessa; Beckett, Sean; Wasserman, Herman
This article challenges the traditional role ascribed by liberal and developmental media theory that journalists should either be watchdogs or developmental journalists but not both at the same time. As part of the South African leg of the Worlds of Journalism (WJS) project this article argues that it is indeed possible that the media can fulfil both roles. Utilizing the WJS 2014 questionnaire and based on a provincial face-to-face (n=37) and a national electronic survey (n=371) the results from the WJS South African project show a potential new trend in the way South African journalists see their role. This article reports in the main on the background to the face-to-face survey, while utilizing data from the national survey reported on elsewhere. Data analysis showed when both roles were compared to one another it was apparent that the watchdog and developmental roles were statistically significantly related to one another.